FRENCH COLONIALISM INFLUENCE ON POSTCOLONIAL RULING ELITE TRANSFORMATION IN IVORY COAST - MAZGELYTĖ, RŪTA (Politologija, 2013)
The article adapts insights from the classical approach to power balance and from a critical approach to structural mechanisms in the construction of power (hegemony) to investigate the case of Ivory Coast. The main problem in the case of Ivory Coast is that the state of its habitants was politically re-engineered through the concept of Ivoirite. Such a state widens the gap between citizens and “non-citizens anymore” or “citizens under question” and consolidates dominance relations. The object of this article is the transformation of the ruling elite in Ivory Coast. The author aims to analyze the influence of the French colonialism on the transformation of the ruling elite’s dominance in Ivory Coast. The main objectives are to analyze how the French colonialism forms its dominance and to analyze the dominance dynamics of the postcolonial ruling elite in Ivory Coast. Taking into consideration the specifics of the topic, the author substantially relies on secondary information sources and analyses them employing comparative and interpretative research methods. The first part highlights how the French colonialism was maintaining relations of dominance not only between the colonists and the colonized, but also among local colonial habitants through the education and administration systems’ organization. The focus of the second part is on the transformation of the Ivory Coast ruling elite in the single-party and multi-party regimes. This research has revealed that the French colonialism maintained the exclusivity of local elites at the expense of other colonial habitants through a dualistic approach towards locals by organizing education and administrative activities. One-sided economic and regional priorities created conditions for the local economic elite growth on the ethnic base. The postcolonial ruling elite of Ivory Coast has split on the ethnic basis. Parties as channels to the ruling elite became ethnically clustered. The prolonged dominance of the Baoule ethnic group in the ruling elite and the recent emergence of a reshaped ruling elite reflect the regional and economic distinction rooted in colonial times.